Effect of dietary Chromium, vitamin E and Selenium supplementation on biochemical and physiological parameters of Holstein Friesian cows under heat stress - RAGHUNANDAN, T; SULTANA, J RAZIA; CHANDRA, A SARAT; PRAKASH, M GNANA; VENKATESWARLU, M; RAMANA, D B V (The Indian Journal of Animal Sciences, 2022)
A study was carried out for a period of 90 days during the summer season with the inclusion of chromiumpropionate and vitamin E with selenium, in the feed to investigate their effect on 24 uniparous lactating HolsteinFriesian cows in an early phase of lactation. Cows were randomly assigned to four supplemental doses of 0 (T0);500 IU/animal/day of vitamin E and 0.3 mg/kg DM of selenium (T1); 0.5 mg/kg DM of chromium propionate (T2)and 0.5 mg/kg DM of chromium propionate, 500 IU/animal/day of vitamin E and 0.3 mg/kg DM of selenium (T3).The mean THI value in the morning was 75.10±0.42 and 80.01±0.64 in the afternoon indicating that the animals wereunder mild to moderate heat stress. Increase in the DMI was found in the supplemented groups with a significantdifference between control and T3 group. Milk yield differed significantly between the control and supplementedgroups. The hematological profile did not vary significantly among the groups. Supplementation of chromium alongwith vitamin E and selenium decreased the cortisol level and glutathione peroxidase activity signigicantly in theT3 group. Chromium supplemented groups (T2 and T3) showed greater increase in mean total protein, albuminconcentration and A/G ratio. However, the mean values for thyroid profile, liver enzymes, superoxide dismutase,catalase, globulin, total cholesterol, triglycerides, glucose, urea, creatinine were comparable among the four groups.Statistical analysis revealed that the rectal temperature, respiratory rate, and pulse rate in supplemented groups were significantly reduced. The findings showed that chromium supplementation plays a significant role in alleviating thermal stress and is further more beneficial when supplemented with proven antioxidants vitamin E and selenium.